2012
DOI: 10.1186/1475-2875-11-11
|View full text |Cite
|
Sign up to set email alerts
|

A review of malaria vaccine clinical projects based on the WHO rainbow table

Abstract: Development and Phase 3 testing of the most advanced malaria vaccine, RTS,S/AS01, indicates that malaria vaccine R&D is moving into a new phase. Field trials of several research malaria vaccines have also confirmed that it is possible to impact the host-parasite relationship through vaccine-induced immune responses to multiple antigenic targets using different platforms. Other approaches have been appropriately tested but turned out to be disappointing after clinical evaluation.As the malaria community conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
182
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(193 citation statements)
references
References 156 publications
(151 reference statements)
2
182
0
9
Order By: Relevance
“…Hodder et al , 2001; Miura et al , 2009; Reiling et al , 2012; Schwartz et al , 2012). In a new study, however, Boyle et al (2015) demonstrated that acquired invasion‐inhibitory antibodies act through binding of C1q and activation of the classical complement pathway rather than by functionally inhibiting invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Hodder et al , 2001; Miura et al , 2009; Reiling et al , 2012; Schwartz et al , 2012). In a new study, however, Boyle et al (2015) demonstrated that acquired invasion‐inhibitory antibodies act through binding of C1q and activation of the classical complement pathway rather than by functionally inhibiting invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, RTS,S/AS01E, a vaccine based on the P. falciparum circumsporozoite protein and blood stage parasite proteins, has demonstrated promising results , Agnandji et al 2011, Schwartz et al 2012. Vaccines based on the anti-merozoite surface protein of blood stages (McCarthy et al 2011) and a transmission-blocking vaccine (Herrera et al 2007, Arevalo-Herrera 2010, Gregory et al 2012) are being tested.…”
Section: Malaria Treatment and Drug-resistant Parasites -mentioning
confidence: 99%
“…Despite recent promises exhibited by some of the vaccine candidates, there are no approved malarial vaccines on the horizon (1). The rapid rise in resistance of malaria parasites against existing antimalarial drugs has emerged as a major problem in the treatment of the disease.…”
mentioning
confidence: 99%